The Devil is in the Words: A Cognitive Linguistic Analysis of Populist Discourse and its Pedagogical Implications - Kopeć, Joanna; Przybysz, Aneta (Populismo y propaganda: entre el presente y el pasado, 2020)
The authors propose to analyse the linguistic and conceptual metaphorization of the political life and activity in the language used by the two French populist politicians, Jean-Luc Mélenchon and Marine Le Pen. This study is mainly based on the Conceptual Metaphor Theory, as introduced by Lakoff and Johnson. We analyse the metaphorical language both at the linguistic and at the conceptual level. To make our study more rigorous, we have drawn upon the Metaphor Identification Procedure and Raoul Girardet’s Four Political Myths. Finally, the paper offers some ensuing pedagogical implications.